Embracing the knowledge economy : the dynamic transformation of the Finnish innovation system - Schienstock, Gerd. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2004)
This book offers a comprehensive appraisal of the management of Finland's transition to a knowledge society. Business managers, policymakers and scholars in the fields of institutional economics, innovation management and political science will welcome this coherent description of Finland's successful search for a new development path.
Includes index.
rpm 22/10/13
Loans
Keywords: Information technology -- Economic aspects -- Finland; Industrial policy -- Finland; Technological innovations -- Economic aspects -- Finland; Knowledge management -- Finland; Finland -- Economic policy